Carcinoid-Like/Labyrinthine Pattern in Sebaceous Neoplasms Represents a Sebaceous Mantle Phenotype: Immunohistochemical Analysis of Aberrant Vimentin Expression and Cytokeratin 20-Positive Merkel Cell Distribution. (November 2017) - Goto, Keisuke; Anan, Takashi; Fukumoto, Takaya; Kimura, Tetsunori; Misago, Noriyuki
Abstract : Abstract: This study investigated the nature of carcinoid-like, labyrinthine, rippled, and conventional cell arrangements in sebaceous neoplasms, focusing on vimentin expression and Merkel cell distribution in sebaceous neoplasms relative to these findings in normal sebaceous units and other sebaceous conditions. Immunohistochemistry for vimentin and cytokeratin 20 (CK20) was evaluated in carcinoid-like (n = 2), labyrinthine (n = 4), rippled (n = 3), and conventional (n = 6) sebaceomas; sebaceous mantle hyperplasia (n = 1); steatocystomas (n = 5); fibrofolliculomas (n = 4); sebaceous mantleoma (n = 1); sebaceous gland hyperplasias (n = 4); sebaceous adenomas (n = 4); and sebaceous carcinomas (n = 4) as well as normal skin tissue. The sebaceous mantle and its hamartoma (fibrofolliculoma) showed weak positivity for vimentin in the basal layer of the epithelial component and contained a few CK20-positive Merkel cells within the epithelial component, whereas mature sebaceous lobules were negative for vimentin and did not contain any Merkel cells. All sebaceomas with carcinoid-like or labyrinthine pattern highly expressed vimentin. CK20-positive Merkel cells were distributed with varying numbers in carcinoid-like pattern (2/2) and labyrinthine pattern (3/4) sebaceomas, sebaceous mantle hyperplasia (1/1), steatocystomas (3/5), fibrofolliculomas (3/4), and sebaceous mantleoma (1/1). Vimentin expression and Merkel cell distribution were observed in normal sebaceous mantles and sebaceous mantle–associated lesions, which could be evidence of a sebaceous mantle nature in the limited setting of sebaceous lesions. Furthermore, carcinoid-like/labyrinthine pattern sebaceomas also showed vimentin immunoreactivity and contained Merkel cells. Therefore, carcinoid-like/labyrinthine pattern of cell arrangement in sebaceous neoplasms may represent a morphological phenotype of sebaceous mantles.